EFFECTIVENESS OF AGRICULTURAL EXTENSION IN THE PRODUCTION OF DATE PALM CROP AT BAHARIYA OASIS IN GIZA GOVERNORATE - Samia Mahros (Arab Universities Journal of Agricultural Sciences, 2018)
The current research was conducted to determine the degree of effectiveness of agricultural extension in date palm production, determining the relationship between the independent variables studied and the effectiveness of agricultural extension in the production of palm date palm, identifying the problems facing the farmers, to achieve the research objectives, Bahariya Oasis at Giza governorate was selected as a geographic field for the study sample, a systematic random sample of 235 farmers representing (10%) of the farmers totaled 2350 at the study area. Data were collected through the personal interview with the sample research using a questionnaire. Frequencies, percentage, range, arithmetic mean, standard deviation, analysis of variance, simple correlation coefficient (Pearson), and step-wise regression analysis were utilized to present and analyze data.  Results showed that (51.4%) of the respondents fell under the medium category of indicator of  the degree of effectiveness of agricultural extension in date palm production, and (37.6%) of them fell under the low category of the indicator, while (11%) of the total sample fell under the high category of the indicator.  Results indicate that the degree of effectiveness of extension activities in the date palm production was significant at 0.01 for each of the researcher's education, the date of agricultural tenure of date palms, the number of years of experience in date palm cultivation and the driving grade, while the number of years of experience in agricultural work, the degree of trend towards agricultural innovations and the degree of orientation towards extension were significant at 0.05.  Results also showed four variables out of the total independent variables which explain around (43.8%) of the total variation of effectiveness of extension activities in the date palm production using the Step Wise regression i.e. the date of agricultural tenure of date palms, the number of years of experience in date palm cultivation, the researcher's education and the degree of trend towards agricultural innovations.